2018
DOI: 10.1142/s0218957718500100
|View full text |Cite
|
Sign up to set email alerts
|

Practical Considerations for Standardized Recording of Muscle Mechanical Properties Using a Myometric Device: Recording Site, Muscle Length, State of Contraction and Prior Activity

Abstract: Purpose: This study aimed to systematically examine the influence of various muscle and experimental conditions on Myoton recordings. Methods: A cross-sectional, observational design was used to examine muscle conditions and experimental factors (different recording sites, muscle length, level of contraction and prior physical activity) that may influence reproducibility of Myoton recordings for biceps brachii (BB) and rectus femoris (RF). Fifty-three healthy adults (26 young, 27 older) aged 18–90 years were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 28 publications
2
30
3
Order By: Relevance
“…While fat thickness may be potentially associated with muscle parameters in certain cases [ 39 ], it is difficult to conclude that fat thickness influences muscle parameters directly due to inconsistences across age and gender groups [ 40 ]. A recent study in healthy participants reported that probe positioning away from the muscle midpoint, alteration in muscle length, level of contraction, and prior physical activity significantly altered mechanical tone and stiffness of biceps brachii and rectus femoris muscles [ 18 ]. In recognizing factors that influence muscle parameters, it is important to consider the technique utilised for assessing these to provide a context [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While fat thickness may be potentially associated with muscle parameters in certain cases [ 39 ], it is difficult to conclude that fat thickness influences muscle parameters directly due to inconsistences across age and gender groups [ 40 ]. A recent study in healthy participants reported that probe positioning away from the muscle midpoint, alteration in muscle length, level of contraction, and prior physical activity significantly altered mechanical tone and stiffness of biceps brachii and rectus femoris muscles [ 18 ]. In recognizing factors that influence muscle parameters, it is important to consider the technique utilised for assessing these to provide a context [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The device elicits oscillations of muscle after a probe applies a brief mechanical impulse following a constant pre-load to the skin over the muscle. From these oscillations, the device quantifies various parameters simultaneously, including non-neural tone and mechanical properties such as dynamic stiffness and decrement [ 18 ]. The frequency determined by fast Fourier transform (FFT) which was most characteristic in the registered oscillation acceleration signal, indicates resting tone or state of tension of an activated muscle (Fmax; (Hz)).…”
Section: Methodsmentioning
confidence: 99%
“…The muscle tone can be classified as neural and non-neu- [32]. Greater muscle tone as observed in the TA, GM, and RF muscles in all participants could be associated with a smaller cross-sectional area or whether these muscles were relaxed in resting position or not [33]. However, we did not directly measure the cross-sectional area of the muscles or used EMG to predict muscular activation in resting position.…”
Section: Discussionmentioning
confidence: 97%
“…Our results showed normalization of basal tone (F), plasticity (D), and stiffness (S) in the EX and CT with respect to the GM, which was used as the reference in the MyotonPro analysis. 35 Thus, it is not possible to conclude that VISS is better than the home-based exercises that were proposed to the patients. Nevertheless, the EX experienced major changes in rheological properties of the muscle with versus the CT, except for GMDR (group p = 0.60).…”
Section: Discussionmentioning
confidence: 99%